Flood-tolerant rice for enhanced production and livelihood of smallholder farmers of Africa - Mwakyusa, Lupakisyo; Dixit, Shalabh; Herzog, Max; Heredia, Maria C.; Madege, Richard R.; Kilasi, Newton L. (Frontiers Media, 2023)
Climate change has intensified food security challenges, especially in Africa, where a significant portion of produce is reliant on smallholder farmers in rainfed conditions. Prolonged flooding and droughts, driven by erratic weather patterns, have significantly elevated the risk of food scarcity. Floods, in particular, have been responsible for severe crop losses, raising concerns about increasing import costs if this issue is not mitigated. Africa is actively working to mitigate the impacts of flooding and enhance food security, although progress has been gradual. Developing flood-resilient varieties is a promising strategy to address this challenge. We explored various flood types common in the region and observed a scarcity of research on flood-resilient varieties, particularly those adapted for anaerobic germination and stagnant flooding. Conversely, varieties bred for flash flooding, such as FARO 66 and FARO 67, have seen limited distribution, primarily confined to a few West African countries, falling short of the intended impact. In contrast, deepwater tolerance research dates back to the early 1900s, but commercialization of the varieties remains limited, with scarce information regarding their cultivation, coverage, and performance. Newly developed varieties, such as Kolondieba 2 and Kadia 24, have received less attention, leaving many farmers dependent on locally adapted cultivars specific to particular areas. Remarkably, despite the limited information, both released and local stress-tolerant cultivars exhibit substantial survival rates and yield advantages. For instance, FARO 66 and FARO 67 have demonstrated 1–3 t/ha yield advantages over recurrent parents under flooding stress. Nonetheless, further efforts are required to address various forms of flooding. To this end, AfricaRice collaborates with National Rice Development Strategies, IRRI, and other partners to promote research and development. While improved flood-tolerant varieties remain limited in scope across Africa, the financial gains for farmers are significant when compared to susceptible cultivars. As the continent’s population continues to grow rapidly, there is untapped potential in African germplasms, making ongoing research and breeding strategies essential. Therefore, this review highlights the importance of intensifying efforts in screening and identifying flood-tolerant rice. Furthermore, it underscores the value of utilizing traditional flood-resilient cultivars in breeding to enhance the productivity of widely distributed and cultivated varieties.